Porous Materials: Copper Conversion into Cu(OH)2 Nanotubes for Positioning Cu3(BTC)2 MOF Crystals: Controlling the Growth on Flat Plates, 3D Architectures, and as Patterns (Adv. Funct. Mater. 14/2014). (April 2014) - Okada, Kenji; Ricco, Raffaele; Tokudome, Yasuaki; Styles, Mark J.; Hill, Anita J.; Takahashi, Masahide; Falcaro, Paolo
<x xml:space="preserve">Abstract</x> Controlling metal–organic framework (MOF) growth on different substrates is crucial for device fabrication. An Australian–Japanese collaboration between M. Takahashi, P. Falcaro, and co‐workers demonstrates on page 1969 how MOF coatings on flat plates, 3D surfaces, and patterns can be fabricated using a facile, two‐step conversion process at room temperature with aqueous/alocholic solutions. Using copper substrates, nanotubes are grown and then quickly converted to MOF crystals, and MOF patterns are fabricated using sunlight. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>